Highly stable tetradentate phosphonate-based green fluorescent Cu-MOF for anticancer therapy and antibacterial activity. (June 2022) - Chakraborty, D.; Musib, D.; Saha, R.; Das, A.; Raza, M.K.; Ramu, V.; Chongdar, S.; Sarkar, K.; Bhaumik, A.
Abstract: Metal-organic frameworks (MOFs) have attracted huge attention in drug delivery, cellular imaging, and anticancer therapy due to their exceptionally high surface area, large internal void space, and the possibility of building the frameworks with fluorescent ligands. Here we demonstrate the synthesis of a highly stable tetradentate phosphonate ligand-based green fluorescent bioactive Cu-MOF (H8 L-Cu-Crystal) in a water medium. This new MOF displayed monoclinic crystal structure [empirical formula: C13 H13 CuO7 P2, H2 O; space group C2/c ; a  = 27.9337 Å, b  = 12.094 Å, c  = 10.560 Å; α  =  γ  = 90°, β  = 99.607° unit cell volume = 3517.3 Å 3 ; CCDC No. 1922965] having theoretical surface area of 164 m 2 /g with optimized energy 1475.9634 a.u. and HOMO-LUMO gap at 3.6 eV. Upon visible light irradiation, Cu-MOF generates highly reactive singlet oxygen ( 1 O2 ) species, which exhibits a superior photocytotoxic effect against human lung epithelial cancer cells (A549) with respective IC50 value = 15.96 μg/mL and nominal dark toxicity of IC50  = 225 μg/mL. Notably, the tetradentate phosphonate moiety in the MOF crystal acts as a ﬂuorophore, which is beneficial for cancer cell imaging. Due to active surface area, reactive oxygen species (ROS) generation, porosity, and Cu-ion metal center, the MOF exerts excellent antibacterial efficacy against both Gram-positive and Gram-negative microorganisms. Minimum inhibitory concentrations (MICs) are recorded at 300 μg/mL and 350 μg/mL for Escherichia coli (ATCC 8739) and Staphylococcus aureus (ATCC 25923), respectively. SEM images reveal dead and deformed bacterial cellular morphologies. What's more, the MOF crystal shows a good binding affinity coefficient value ( K BSA  = 4.8 × 10 4  M −1 ) with bovine serum albumin (BSA) protein interaction. Overall, these results suggest that this Cu-phosphonate MOF is a promising aspirant for anti-cancer photodynamic therapy and bacterial eradication. Graphical abstract: We report a tetradendentate phosphonate ligand-based new Cu-MOF (H8 L-Cu-Crystal) with monoclinic crystal structure, which generated highly reactive singlet oxygen ( 1 O2 ) species upon visible light irradiation and it exhibited signiﬁcant photocytotoxic effect in human lung epithelial (A549) cancer cells. Image 1 Highlights: Tetraphosphonate ligand-based MOF H8 L-Cu-Crystal has been synthesized. This Cu-MOF is stable at high temperature and in different polar/nonpolar solvents. Cu-MOF initiates ROS production and photocytotoxic effect against A549 cancer cells. Cu-MOF exhibits antibacterial efficacy against different microorganisms.